Nanomolar Protein Thermal Profiling with Modified Cyanine Dyes - Malakoutikhah Morteza; Mahran Randa; Gooran Negin; Masoumi Ahmadreza; Lundell Katri; Liljeblad Arto; Guiley Keelan; Dai Shizhong; Zheng Qinheng; Zhu Lawrence; Shokat Kevan M.; Kopra Kari; et al. (American Chemical Society, 2025)
Protein properties and interactions have been widely investigated by using external labels. However, the micromolar sensitivity of the current dyes limits their applicability due to the high material consumption and assay cost. In response to this challenge, we synthesized a series of cyanine5 (Cy5) dye-based quencher molecules to develop an external dye technique to probe proteins at the nanomolar protein level in a high-throughput one-step assay format. Several families of Cy5 dye-based quenchers with ring and/or side-chain modifications were designed and synthesized by introducing organic small molecules or peptides. Our results showed that steric hindrance and electrostatic interactions are more important than hydrophobicity in the interaction between the luminescent negatively charged europium-chelate-labeled peptide (Eu-probe) and the quencher molecules. The presence of substituents on the quencher indolenine rings reduces their quenching property, whereas the increased positive charge on the indolenine side chain improved the interaction between the quenchers and the luminescent compound. The designed quencher structures entirely altered the dynamics of the Eu-probe (protein-probe) for studying protein stability and interactions, as we were able to reduce the quencher concentration 100-fold. Moreover, the new quencher molecules allowed us to conduct the experiments using neutral buffer conditions, known as the peptide-probe assay. These improvements enabled us to apply the method in a one-step format for nanomolar protein-ligand interaction and protein profiling studies instead of the previously developed two-step protocol. These improvements provide a faster and simpler method with lower material consumption.